Desenvolvimento do Turismo e Efeitos sobre o Ambiente Econômico Urbano: Análise de Estudos Indexados na Base Scopus / Tourism Development and its Effects on the Urban Economic Environment: Indexed Studies Analysis in Scopus Database - Guizi, Alan Aparecido (Revista Rosa dos Ventos - Turismo e Hospitalidade, 2019)
RESUMO O presente estudo volta-se para a compreensão do desenvolvimento da atividade turística e possíveis impactos sobre o ambiente econômico urbano, por meio de pesquisa e coleta de estudos publicados em periódicos estrangeiros indexados na plataforma de pesquisa Scopus. Apresenta-se a análise dos artigos coletados em quatro seções temáticas distintas, porém interligadas, com foco econômico, além do marco teórico relacionado ao turismo em áreas urbanas, para embasar as análises e compreensão do tema proposto. Ao final, notou-se que, para muitos contextos de destinos, o turismo é compreendido como uma atividade de considerável importância econômica, mas carece de planejamento detalhado e sistemático com vistas a prever e mitigar efeitos nocivos da atividade sobre a cidade, para além dos fatores econômicos, como os sociais e culturais. PALAVRAS-CHAVE Turismo Urbano. Urban Tourism. Desenvolvimento. Development. Economia Urbana. Urban Economy. Scopus. ABSTRACT This study aimed to understand the tourism activity development and its possible impacts on the urban economic environment, through research and collection of studies published in international journals and indexed in the Scopus research platform, presenting papers collected analysis through four different thematic sections but interconnected, with economic focus, as well a theoretical description about tourism in urban areas, to provide background to the analysis and comprehension of this topic. In the end, was observed that for many destinations around the world, tourism is seen as an important economic activity, but it’s necessary a detailed and systematic planning to predict and mitigate the harmful effects, not only to the urban economy, but also to social and cultural factors in a city. KEYWORDS Urban Tourism. Development. Urban Economy. Scopus. AUTORIA Alan Aparecido Guizi – Mestre. Doutorando, Universidade de Aveiro, Portugal. Professor na Universidade Anhembi Morumbi, São Paulo, São Paulo, Brasil. Currículo: http://lattes.cnpq.br/0290102758341785 E-mail: alanguizi@gmail.com REFERENCIAS Acerenza, M. Á. (2006). Conceptualización, origen Y evolución del turismo. México: Trillas. Aliaskarov, D., Beisenova, A., Irkitbaev, S., Atasoy, E., & Wiskulki, T. (2017). Modern changes in Zhezkazgan City: Positive and negative factors of tourism development (Kazakhstan). GeoJournal of Tourism and Geosites, 20(2), 243–253. Link Ashworth, G., & Page, S. J. (2011). Urban tourism research: Recent progress and current paradoxes. Tourism Management, 32(1), 1-15. Link Buhalis, D. (2000). Marketing the competitive destination of the future. Tourism Management, 21(1), 97-116. Link Butler, R. W. (1980). The Concept of an Area Cycle Of Evolution: Implications for management of resources. Canadian Geographer, 24, 5-12. Link Chang, T. C., Milne, S., Fallon, D., & Pohlmann, C. (1996). Urban heritage tourism. Annals of Tourism Research, 23(2), 284-305. Link Chapman, A., & Light, D. (2016). Exploring the tourist destination as a mosaic: The alternative lifecycles of the seaside amusement arcade sector in Britain. Tourism Management, 52(February), 254-263. Link Deng, H., Liu, T., & Zhao, J. (2011). Strategic measures for an integrated approach to sustainable development in Lijiang City. International Journal of Sustainable Development and World Ecology, 18(6), 559-562. Link Fillipim, M., Hoffmann, V., & Alberton, A. (2006). Turismo rural em fazendas-hotel: um estudo das características da demanda e fatores de influência no Planalto Serrano e Meio-Oeste de SC. Turismo - Visão e Ação, 8(1), 31-46. Link Fistola, R., & La Rocca, R. A. (2017). Driving functions for urban sustainability: The double-edged nature of urban tourism. International Journal of Sustainable Development and Planning, 12(3), 425-434. Link Garrigós-Simón, F. J., Galdón-Salvador, J. L., & Gil-Pechuán, I. (2015). The economic sustainability of tourism growth through leakage calculation. Tourism Economics, 21(4), 721-739. Link Gotham, K. F. (2005). Tourism from above and below: Globalization, localization and New Orleans’s Mardi Gras. International Journal of Urban and Regional Research, 29(2), 309-326. Link Hampton, M. P. (2003). Entry points for local tourism in developing countries: Evidence from yogyakarta, Indonesia. Geografiska Annaler, Series B: Human Geography, 85(2), 85-101. Link Hayllar, B., & Griffin, T. (2005). The precinct experience: A phenomenological approach. Tourism Management, 26(4), 517-528. Link Joksimović, M., Golić, R., Vujadinović, S., Šabić, D., Jovanović Popović, D., & Barnfield, G. (2014). Restoring tourist flows and regenerating city’s image: the case of Belgrade. Current Issues in Tourism, 17(3), 220-233. Link Khazaei, A., Elliot, S., & Joppe, M. (2015). An application of stakeholder theory to advance community participation in tourism planning: the case for engaging immigrants as fringe stakeholders. Journal of Sustainable Tourism, 23(7), 1049-1062. Link Li, L., & Tao, W. (2003). Spatial structure evolution of system of recreation business district. Chinese Geographical Science, 13(4), 370-377. Link Liu, Y. De. (2010). Planning considerations of urban cultural tourism: a case study of four UK cities. International Journal of Tourism Policy, 3(2), 113-124. Link Martí, P., Nolasco-Cirugeda, A., & Serrano-Estrada, L. (2017). Assessment tools for urban sustainability policies in Spanish Mediterranean tourist areas. Land Use Policy, 67(April), 625-639. Link Mbaiwa, J. E., Toteng, E. N., & Moswete, N. (2007). Problems and prospects for the development of urban tourism in Gaborone and Maun, Botswana. Development Southern Africa, 24(5), 725-740. Link Merinero-Rodríguez, R., & Pulido-Fernández, J. I. (2016). Analysing relationships in tourism: A review. Tourism Management, 54, 122-135. Link Miralles, J., & García-Ayllón, S. (2013). The economic sustainability in urban planning: The case of La Manga. Sustainable Development and Planning, 173, 575-587. Link Opschoor, H., & Tang, L. (2011). Growth, world heritage and sustainable development: The case of Lijiang City, China. International Journal of Sustainable Development and World Ecology, 18(6), 469-473. Link Page, S. (1989). Tourist development in London Docklands in the 1980s and 1990s. GeoJournal, 19(3), 291-295. Link Razali, M. K., & Ismail, H. N. (2014). A sustainable urban tourism indicator in Malaysia. WIT Transactions on Ecology and the Environment, 187(6), 133-145. Link Santos, M. (2003). Economia espacial: críticas e alternativas. São Paulo: Edusp. Severo, E. A., Dorion, E. C. H., Guimarães, J. C. F. d., Souza, R. A. d., & Severo, P. O. (2016). Trajetórias da inovação : uma análise na base de dados Scopus. Revista Espacios, 37(11), 1-13. Link Sheng, L. (2011). Foreign investors versus local business: An urban economics model for tourist cities. International Journal of Tourism Research, 13(July 2010), 32-40. Link Steel, G. (2013). Mining and tourism: Urban transformations in the intermediate cities of Cajamarca and Cusco, Peru. Latin American Perspectives, 40(2), 237-249. Link UNWTO - United Nations World Tourism Organization (2017). UNWTO Annual Report 2016. Link Upchurch, R. S., & Teivane, U. (2000). Resident perceptions of tourism development in Riga, Latvia. Tourism Management, 21(5), 499-507. Link WTTC - World Travel & Tourism Council. (2018). Travel & Tourism: Economic Impact 2018 World. London. Link Xiao, G., & Wall, G. (2009). Urban tourism in Dalian, China. Anatolia, 20(1), 178-195. Link PROCESSO EDITORIAL Recebido: 5 MAI 18; Avaliado: FEV-ABR; Aceito: 15 JUL 19